Unlocking insights: A systematic review of contextualized cubing instructional strategies - Sam Ramaila (African Journal of Teacher Education)
This systematic review examines the effectiveness of contextualized instructional strategies in the domain of cubing. Cubing, a popular puzzle-solving activity, has garnered significant attention in educational settings as a tool for enhancing spatial reasoning and problem-solving skills. However, the efficacy of different instructional approaches in facilitating cubing mastery remains underexplored. Through a comprehensive analysis of existing literature, this review synthesizes evidence on the impact of contextualized instructional strategies on learners' cubing proficiency. Drawing from a range of studies, including experimental interventions, comparative analyses, and qualitative investigations, key themes emerged regarding the benefits of contextualized instruction in enhancing learners' understanding of cubing algorithms, spatial visualization abilities, and overall problem-solving competence. Additionally, this review identifies gaps in the current literature and offers insights for future research directions, highlighting the importance of tailored instructional approaches that integrate real-world contexts to optimize cubing learning outcomes. Overall, this study provides valuable insights for educators, researchers, and practitioners seeking to enhance cubing instruction through evidence-based pedagogical strategies.